Pengaruh Manajemen Pengetahuan Terhadap Inovasi: Kasus Industri IT di Indonesia - Gidionton Saritua Siagian; Zulfa Fitri Ikatrinasari (Universitas Mercu Buana, 2019)
The purpose of this journal is to examine the effect of the relationship between knowledge management and innovation in companies based on IT in Indonesia. This study uses the SEM (Structured Equation Modeling) method using PLS software based on primary data from the questionnaire. Based on the results of the study, it was found that the influence of knowledge management on innovation was significantly positive. This can be seen from the relationship between dimensions that is quite strong, where knowledge management has a very positive impact on the dimensions of process innovation and dimensions of product innovation. The proposed framework can be used to guide the development of strategies for implementing knowledge management to enhance the competitiveness of companies through innovation.